ANALISIS SISTEM ANTRIAN PESAWAT TERBANG DI BANDARA INTERNASIONAL AHMAD YANI SEMARANG - Anggit Ratnakusuma; Abdul Hoyyi; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Long queuing is not expected by anyone, because it’s taking much time and tiresome. However, this situation is not avoidable in public area, for example Ahmad Yani International Airport Semarang. Aircraft queuing that will take off and landed resulted in increasing of the queuing of passengers to aboard. The suitable queuing system model for Ahmad Yani Internasional Airport Semarang to solve its air traffic is using (M/M/6):(GD/∞/∞), with six aprons as server of reguler commercial flight. Moreover, based on the result of system performance measure, service system in Ahmad Yani Internasional Airport Semarang report is good enough. The result of system performance measure said that average number of aircraft in the system (Ls) was 1,0716 aircraft per hour, average number of aircraft in the queue (Lq) was 0,0002 aircraft per hour, average time aircraft spends in the system (Ws) was 0,4977 from an hour, and average time aircraft spends in the queue (Wq) was 0,0001 from an hour. The simulation showed that by using four operating server or adding two more arrival additionals in every hour, the service system is quite effective. Keywords: Queuing System Model, Ahmad Yani International Airport Semarang